2012
DOI: 10.3109/17482968.2012.662688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genetic background on onset and disease progression in the SOD1-G93A model of amyotrophic lateral sclerosis

Abstract: Knowledge of the potential effect of genetic background in disease models is important. The SOD1-G93A transgenic mouse is the most widely used model in amyotrophic lateral sclerosis (ALS). Since these animals show considerable variability both in the onset and the progression of the disease, this study aimed to characterize the potential differences between the two most widely used strains, C56BL/6 (B6) and B6SJL. A rotarod test was carried out to assess strength and motor coordination, while electrophysiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 39 publications
3
33
3
1
Order By: Relevance
“…The double transgenic mice are on a C57BL6 background and this genetic background is associated with longer survival and milder disease phenotype [44][45][46], which is opposite from what we observed in double transgenic mice. Therefore, our results strongly suggest that H63D HFE is a contributing factor in ALS disease pathogenesis.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The double transgenic mice are on a C57BL6 background and this genetic background is associated with longer survival and milder disease phenotype [44][45][46], which is opposite from what we observed in double transgenic mice. Therefore, our results strongly suggest that H63D HFE is a contributing factor in ALS disease pathogenesis.…”
Section: Discussioncontrasting
confidence: 84%
“…Genetic background can influence disease onset, severity, and survival in ALS rodent models independent of transgene copy numbers [44][45][46]. The double transgenic mice are on a C57BL6 background and this genetic background is associated with longer survival and milder disease phenotype [44][45][46], which is opposite from what we observed in double transgenic mice.…”
Section: Discussioncontrasting
confidence: 83%
“…At 16 weeks of age, there was a 30 % increase in the number of surviving MNs in the spinal cord of both male and female SOD1 animals treated with PRE-084 with respect to untreated animals. We have previously described the progression of spinal MN degeneration of SOD1 G93A mice, showing that the number of surviving MNs per lumbar cord section averaged 37±2 and 33±3 in male and female mice, respectively, at 12 weeks of age, and 16±2 and 20±1 in male and female mice at 16 weeks of age [23,44], respectively. In the present study, we found that PRE-084 treated animals had a mean of 35±1 (males) and 34±2 (females) MNs per section at 16 weeks of age.…”
Section: Discussionmentioning
confidence: 91%
“…Superoxide dismutase 1 (SOD1) is a ubiquitous cytosolic enzyme; mutations in the Cu/Zn Sod1 gene are a common cause of familial cases of this disease [1, 2]. Transgenic mice expressing the mutated human Sod1 gene are used as a classical model of ALS, in terms of both the mechanism and treatment [3, 4]. The mutant gene shows a toxic gain of function phenotype, which leads to paralysis and death from respiratory failure in the animal model [5].…”
Section: Introductionmentioning
confidence: 99%